Giant Basal Cell Carcinoma of the Scalp with Intracranial Invasion: MRI Findings with Tract Visualisation - Maria Brunella Cipullo; Elham Rahimian; Majid Tahsini; Zoi Giavri; Sotirios Bisdas (Case Reports in Radiology)
A rare case of recurrent basal cell carcinoma in the scalp that infiltrated multiple intracranial structures is presented. Basal cell carcinoma represents one of the most frequent malignant nonmelanotic skin neoplasms, but the majority of them have no aggressive and recurrent behaviour. The aim of this case report is to provide an overview of the main clinical and radiologic features of basal cell carcinoma, focusing on the conventional and advanced (tractography) MRI findings and providing an overview of treatment and prognosis.